You are on page 1of 8

University Of Leicester Department of Economics

EC3001 Advanced Macroeconomics Mathematical Primer: First-Order Difference Equations
Dr. Dimitrios Varvarigos

A first-order difference equation gives the value of a variable x at some reference point t + 1 as a function of the value of the same variable at the reference point t . So, a first order difference equation has the general form x t +1 = F ( x t ) . For our purposes, the reference point will denote a
time period and will be indexed t = 0,1,..., ∞ . The equilibrium in first order difference equations

ˆ. (otherwise known as the ‘steady-state’) is any point that satisfies x t +1 = x t = x

1 Linear first-order difference equations
The general form for the linear case is given by

x t +1 = α + βx t ,

(1.1)

where α > 0 and β > −1 are constant parameters and the initial value x 0 > 0 is given. Given equation (1), the steady state equilibrium is

ˆ = α + βx ˆ⇒ x

ˆ= x

α . 1− β

(1.2)

2 Stability of linear difference equations
A very important issue applying to difference equations is the issue of the stability of the steadystate equilibrium. This is because the stability properties indicate how meaningful this long-run

ˆ , the variable will not reach the equilibrium is. To understand this, think that unless x 0 = x
equilibrium automatically. Instead, it will go through an adjustment period which, eventually, may lead to the steady-state only if this represents a stable equilibrium. However, if the stability conditions are not satisfied then the steady-state will never be actually reached: this implies that the long-run equilibrium is trivial. Ideally, we would like to analyse these issues in a formal manner. To do this, we need an expression that relates x t as a function of its initial value x 0 . We can begin by evaluating equation (1.1) at the initial period t = 0 . That is

x 1 = α + βx 0 .

(2.1)

1

Now do the same application for t = 1 . We get
x 2 = α + βx 1 .
Substituting (2.1) in (2.2) yields (2.2)

x 2 = α + β (α + βx 0 ) ⇒
x 2 = α + αβ + β 2 x 0 .
Next, use (2.1) for t = 2 and substitute (2.3). That is (2.3)

x 3 = α + βx 2 = α + β( α + αβ + β 2 x 0 ) ⇒ x 3 = α + αβ + αβ 2 + β 3 x 0 ⇒ x 3 = α(1 + β + β 2 ) + β 3 x 0 (2.4)

From (2.4) you can see a clear pattern emerging – a pattern which facilitates us in making a conclusion about the general result we are going to get without the need of making these substitutions continuously. Particularly, using (2.4) as our guide, we can infer that, for an arbitrary period t , we have

x t = α(1 + β + β 2 + ... + β t −1 ) + β t x 0 .

(2.5)

ˆ , will Now we can examine whether the dynamic adjustment, starting from a point x 0 ≠ x
eventually lead us to the steady-state equilibrium or not. Using equation (2.5), we can get

lim x t = α lim(1 + β + β 2 + ... + β t −1 ) + x 0 lim β t .
t →∞ t →∞ t →∞

(2.6)

As long as

β < 1 , then lim(1 + β + β 2 + ... + β t −1 ) = 1 + β + β 2 + ... =
t →∞

1 1− β

and lim β t = 0 .
t →∞

Applying these results in (2.6), it becomes clear that as t → ∞ , x t → ˆ= it is x

α . However, from (1.2) 1− β

α . We conclude that the dynamics beginning from any x 0 > 0 , will eventually lead 1− β

ˆ . For this reason, we say that x ˆ is a stable equilibrium. us to the steady-state equilibrium x

2

Let
t →∞

us

now

examine

what

happens
t →∞

when

β > 1.

In

this

case,

lim(1 + β + β 2 + ... + β t −1 ) = 1 + β + β 2 + ... → ∞ and lim β t → ∞ . Thus, the dynamics beginning
ˆ . Instead, as t → ∞ , from any x 0 > 0 , will never lead us to the steady-state equilibrium x ˆ is an unstable equilibrium. x t → ∞ . For this reason, we say that x

3 Phase diagrams
Phase diagrams provide a nice illustration of both the long-run (steady-state) equilibrium and the short-run dynamic behaviour (i.e., the transitional dynamics) of a variable generated by a difference equation. The procedure of constructing phase diagrams is the following: 1. Place the x t +1 values on the vertical axis and the x t values on the horizontal axis. 2. Draw the x t +1 = α + βx t schedule. 3. Draw a 45 line beginning from the origin (i.e., a line for which x t +1 = x t ). The points

where the x t +1 = α + βx t schedule crosses the 45 line are steady-state equilibria.

ˆ in the horizontal axis 4. Begin with an arbitrary point for x t ≠ x
until it meets the x t +1 = α + βx t schedule the 45 line

draw a vertical line

subsequently, draw a horizontal line to meet

afterwards, draw a vertical line that meets the x t +1 = α + βx t schedule

then, draw a horizontal line to meet the 45 line…and so on. Below you can see three phase diagrams corresponding to the different scenarios we have for the equation x t +1 = α + βx t .

3

x t +1 x t +1 = x t x t +1 = α + βx t
ˆ x

α

0

ˆ x

xt

Figure 1: 0 < β < 1

x t +1 x t +1 = x t
α
ˆ x

x t +1 = α + βx t

0

ˆ x

xt

Figure 2: −1 < β < 0

4

x t +1

x t +1 = α + βx t x t +1 = x t

α

0

xt
Figure 3: β > 1

4 The case with α = 0
Setting α = 0 in (1.1) yields

x t +1 = βx t .

(4.1)

ˆ is x ˆ = 0 . Once more, the stability You can clearly see that the only value satisfying x t +1 = x t = x
of the steady-state solution depends on the value of β . To see this, set α = 0 in equation (2.5) to get

xt = βt x0 ,
and, subsequently,

(4.2)

lim x t = x 0 lim β t .
t →∞ t →∞

(4.3)

ˆ , i.e., the dynamics As long as β < 1 , then lim β t = 0 . Therefore, as t → ∞ , x t → 0 = x
t →∞

ˆ: x ˆ = 0 is a beginning from any x 0 > 0 , will eventually lead to the steady-state equilibrium x stable equilibrium (note: we do not consider β < 0 now, because it does not make sense if we are interested in non-negative x t 's ).
5

What happens when β > 1 ? Given lim β t → ∞ , the dynamics beginning from any x 0 > 0 , will
t →∞

ˆ = 0 . Instead, as t → ∞ , x t → ∞ : x ˆ = 0 is an never lead to the steady-state equilibrium x unstable equilibrium. With these extreme implications, does the above analysis imply that the case where α = 0 is trivial and unimportant? The answer is ‘no’. This case has important implications for variables that grow over time. To see this, divide both sides of (4.1) with x t and subtract 1 from both sides. This yields

x t +1 x − xt − 1 = t +1 = β −1. xt xt

(4.4)

This expression shows the growth rate of the variable x t and clarifies the reason why we get such extreme implications. On the one hand, for β > 1 the variable has a positive growth rate which implies that it constantly increases in value over time. On the other hand, for β < 1 the variable has a negative growth rate: it constantly declines in value over time until it settles down to zero.

5 Non-linear first-order difference equations
Non-linear difference equations have the form x t +1 = F ( x t ) which satisfies F ′′( x t ) ≠ 0 (the second derivative with respect to x t is not zero). A few examples are the following:
x t +1 = α + βx tm , m ≠ 1 ,

x t +1 = x t (1 − x t ) . ˆ ⇔x ˆ = F(x ˆ ) . However, the Once more, the steady-state is a solution that satisfies x t +1 = x t = x
stability condition is different compared with the linear case. Specifically, the equilibrium is stable as long as ˆ ) < 1⇒ F ′( x
ˆ)<1 −1 < F ′( x

6

holds. Thus, stability requires that the first derivative of F ( ⋅) with respect to x t is below 1 in

ˆ . You do absolute value when evaluated at the steady-state – that is, when evaluated at x t = x
not need to know the proof for this, but for those interested the proof will be presented here.
ˆ . Doing Firstly, we take a first order linear approximation of F ( x t ) around the steady state x

this, we have

ˆ ) + F ′( x ˆ )( x t − x ˆ ), F(xt ) ≃ F(x
ˆ = F(x ˆ ) . Substituting this together with x t +1 = F ( x t ) above, we get The steady-state satisfies x

ˆ ≃ F ′( x ˆ )( x t − x ˆ ). x t +1 − x ˆ , β = F ′( x ˆ ) and substitute above to get Now, denote z t = x t − x z t +1 ≃ βz t .
From the analysis of Section 4, we know that for an equation of this form, a stable steady state

ˆ , β = F ′( x ˆ ) . Therefore, the equilibrium z t = 0 is possible when β < 1 . But recall that z t = x t − x ˆ is stable when F ′( x ˆ) < 1. steady state equilibrium z t = 0 ⇒ x t = x

7